2021
DOI: 10.3389/fonc.2021.672797
|View full text |Cite
|
Sign up to set email alerts
|

Real Life Clinical Management and Survival in Advanced Cutaneous Melanoma: The Italian Clinical National Melanoma Registry Experience

Abstract: BackgroundCutaneous melanoma (CM) is one of the most aggressive types of skin cancer. Currently, innovative approaches such as target therapies and immunotherapies have been introduced in clinical practice. Data of clinical trials and real life studies that evaluate the outcomes of these therapeutic associations are necessary to establish their clinical utility. The aim of this study is to investigate the types of oncological treatments employed in the real-life clinical management of patients with advanced CM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Two studies were excluded as they grouped data for electrochemotherapy with other interventions such as radiotherapy as ‘local therapies’ and any outcomes were inseparable and not suitable for extraction [ 33 , 34 ]. We contacted the authors of these studies to obtain extractable data but did not receive a response.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies were excluded as they grouped data for electrochemotherapy with other interventions such as radiotherapy as ‘local therapies’ and any outcomes were inseparable and not suitable for extraction [ 33 , 34 ]. We contacted the authors of these studies to obtain extractable data but did not receive a response.…”
Section: Resultsmentioning
confidence: 99%
“…Through searching, additional data sets which included groups of patients treated with electrochemotherapy and with radiotherapy were identified, but due to the how the outcomes for these patients were grouped, no data could be extracted to allow indirect comparison [ 33 , 34 ]. Notably, there was no published data from any directly comparative trials between electrochemotherapy and radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…15 It should be noted that patients with stage IIIA disease and lymph-node metastases <1 mm were not eligible for either of these two trials; furthermore, patients with stage IIIA disease were excluded from other adjuvant immunotherapy trials 20,21 and were not included in a recent survival analysis of patients with melanoma receiving adjuvant therapy in a real-world setting. 18 Patient demographics in the MAP were similar to those of DESCRIBE-AD, an observational retrospective study of 65 patients with histologically confirmed and resected BRAF-mutated melanoma previously treated with dabrafenib plus trametinib in the adjuvant setting in Spain, 22 and to those in the COMBI-APlus trial. 13 Moreover, the characteristics of patients enrolled in the MAP were similar to those described in a retrospective analysis of 113 patients with stage III melanoma who received at least one cycle of adjuvant immunotherapy or targeted therapy at two Italian institutions, 19 and an analysis of 787 patients with advanced cutaneous melanoma from the Clinical National Melanoma Registry (CNMR); as previously mentioned, the latter did not include patients with stage IIIA disease.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have been published that describe the adjuvant treatment of patients with melanoma in Italy; 18,19 however, these studies also include patients who received immunotherapy, and -as is often the case in real-world studies -lack information on treatment dosing and schedule, as well as on dose reductions and Our work describes the characteristics and the patient journey of patients with high-risk BRAF V600E/K -mutated melanoma who were treated with adjuvant dabrafenib plus trametinib after surgical resection as part of an Italian MAP. We also included a detailed analysis of the patient subgroup with stage IIIA disease, since this group was not always included in the pivotal clinical studies of adjuvant therapy for melanoma and is not included in some of the recently published real-world evidence studies either.…”
Section: Discussionmentioning
confidence: 99%
“…About 85% of cutaneous melanoma arising annually worldwide affect populations in North America, Europe, and Oceania, with the highest incidence in white people [ 4 ]. In recent years, an increasing trend in the incidence of melanoma has been reported for Europe which will likely continue in the next decades [ 5 ].…”
Section: Introductionmentioning
confidence: 99%